Landscaping macrocyclic peptides: stapling hDM2-binding peptides for helicity, protein affinity, proteolytic stability and cell uptake. Issue 7 (31st May 2022) - de Araujo, Aline D.; Lim, Junxian; Wu, Kai-Chen; Hoang, Huy N.; Nguyen, Huy T.; Fairlie, David P.
Abstract : Surveying macrocycles for mimicking a helical tumor suppressor protein, resisting breakdown by proteases, and entering cancer cells. Abstract : Cyclic peptides that modulate protein–protein interactions can be valuable therapeutic candidates if they can be delivered intact to their target proteins in cells. Here we systematically compare the effects of different helix-inducing cyclization constraints on the capacity of a macrocyclic peptide component to confer α-helicity, protein-binding affinity, resistance to degradative proteases and cell uptake to a 12-residue peptide fragment of tumor suppressor protein p53. We varied the helix-inducing constraint (hydrocarbon, lactam, aliphatic or aromatic thioether, etc. ) and the position of the cyclization linker ( i to i + 4 or i to i + 7 bridges) in order to sculpt the macrocyclic size, stabilize its structure, and promote cell uptake. We find that rigidifying the macrocycle leads to higher alpha helicity, target affinity and proteolytic stability to different extents, whereas cell uptake of compounds shown here is mostly driven by hydrophobicity and aromaticity of the macrocycle.